Model EarthComm Berbantuan Google Earth dalam Pembelajaran Geografi terhadap Sikap Peduli Lingkungan Siswa - Dimas Andre Prasetyo; I Putu Sriartha; Made Dwipayana (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Geography learning in X-IPS class at SMAN 1 Sawan faces the problem of lack of visualisation of the impact of environmental damage due to limited media and classroom-based learning. Students' low awareness of environmental cleanliness is also an obstacle, indicated by the discovery of garbage in the classroom area. This study aims to analyse the effectiveness and influence of the application of EarthComm learning model assisted by Google Earth on the environmental care attitude of 10th grade students at SMAN 1 Sawan. This study used a pseudo-experimental research method with Pretest-Posttest Only Control Group Design. Hypothesis testing was conducted using descriptive analysis for model implementation, N-Gain Score for effectiveness data analysis and t-test for effect test. The results showed that the implementation of the EarthComm learning model assisted by Google Earth was included in the very good category with a score of ’83,33’ in geography learning, quite effective in increasing students' environmental care attitudes with a value of 65.95% in the experimental class compared to 17.8% in the control class, and had a significant effect on students' environmental care attitudes with a sig value of 0.000 <0.05.